Market driven strategy : - Day, George S. (Free Press, 1999)
Now in its 21st printing, George S. Day's Market Driven Strategy first defined what it means to be "market- driven." Providing a foundation for Day's new companion volume The Market Driven Organization, this seminal work remains a vital resource for a generation of managers struggling to align their organizations to volatile markets. Contending that the rate of change in the market has clearly outstripped the speed at which a conventionally managed company can respond, Day makes a compelling case for first creating superior customer value, without which there can be no share-holder value.